Dark Days in Belarus: Surviving the Soviet Hangover in the former USSR's last dictatorship. - Motlagh, Jason (Virginia Quarterly Review)
In an essay the author describes his trip to Belarus, where Alexander Lukashenko, the man often called Europe's last dictator, continues to hold onto power despite protests from political activists. Lukashenko has served as president of the country since 1994, just three years after Belarus attained its independence from the Soviet Union. The article discusses the government's crackdown on protesters and opposition candidates, including Lukashenko's main rival, Vladimir Neklayev. Also discussed is the devastating impact the 1986 Chernobyl nuclear accident had on Belarus.